GRAFTING TECHNIQUES IN CUCURBITS - Shreshtha Das1, Ganisetti Anitha2*, Takhellambam Henny Chanu3, Okram Bijaya Devi4 (Chelonian Research Foundation, 2023)
Grafting is the uniting of two living parts of plant i.e., rootstock and scion. The main aim to adopt various grafting techniques is to avoid soil-borne diseases. In cucurbitaceous crop, due to less arable land and off-season demand the grafting techniques has been adopted. Mainly in watermelon, melon, bitter gourd, summer squash, cucumber of the cucurbitaceous family, grafting is preferred as it showed various resistance to biotic and abiotic stresses. Use of rootstocks can enhance plant vigor by healthy uptake of soil nutrients, avoidance of soil pathogens, salinity, drought, soil varying temperatures and increment in plant production and fruit quality. Grafting was first used in Japan during late 1990’s by grafting watermelon [Citrullus lanatus (Thunb.) Matsum. and Nakai] onto pumpkin [Cucurbita moschata Duchesne ex. Poir] rootstocks. Rootstock-scion combinations has affected the pH, flavor, sugar, carotenoid content, and texture of a fruit in the crop. The rootstock and scion should be chosen with care to control loss. Keywords: Cucurbitaceae, watermelon, cucumber, bitter gourd, summer squash, rootstocks, scion, vigor, carotenoid, biotic stress, abiotic stress